(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The choice that aman has to make to remain true to himself, the corrosion of values in a worldthat puts premium on material success, the human price of ambition in acompetitive society, and the possibility of making an authentic decision in aset up where an individual is allowed very little freedom-these are therecurrent concerns running through his novel – Show Business. Shashi Tharoorshows his socio-Moral vision and mourns for the lack of Dharma in moderntimes. In a Post Modernistic world,where all moral values are gone with the wind, there are very few committedartists with the philosophic vision, who can wage a strong war against theadvent of basic human values. Tharoor considers his art as a medium throughwhich he tries to resurrect the lost dignity of the human being. Art thereforeseems to turn into a didactic weapon by which he reinstates the lost glory ofthe world.